Analisis Konten HOTS dalam Buku Siswa Kelas V Tema 6 “Panas dan Perpindahannya” Kurikulum 2013 - Arif Widodo; Dyah Indraswati; Radiusman Radiusman; Umar Umar; Nursaptini Nursaptini (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2020)
The purpose of this study is to analyze the content or problems presented in a student's book in accordance with the criteria as teaching materials with high-level skills in elementary school. The study uses content analysis methods with stages of data reduction, data presentation and conclusion drawing. Data collection is done by rubrics then presented in graphical form. The data source in this study is the 2013 thematic integrated curriculum book for elementary / MI class V theme 6 "Heat and Displacement". Based on the results of this study it can be seen that in the student book there is a LOTS load of 36%, HOTS content gets a percentage of 64%. The percentage of each cognitive level (C-4) is 35%, Evaluation (C-5) is 33% and Creation (C-6) is 32%. The results of the analysis of these data indicate that in the book students have presented content that contains HOTS and is feasible to be implemented in learning.